Efek Kinesio Taping pada Latihan Penguatan Otot Kuadriseps terhadap Kekuatan Otot Kuadriseps san Status Fungsional Penderita Osteoarthritis Lutut - Anggia P Nayanti; Tertianto Prabowo; Dian M Sari (Journal of Medicine and Health, 2020)
Knee Osteoarthritis (KOA) is characterized by knee cartilage degradation. Knee Osteoarthritis symptoms are joint pain, stiffness, quadriceps muscle weakness and daily activities difficulties. The use of Kinesio Taping (KT) in Quadriceps muscle strengthening exercises (QSE) is known to increase quadriceps muscle strength, reduce pain and improve functional abilities in KOA. This study aimed to determine the effect of KT with QSE on quadriceps muscle strength and functional status in KOA. This is a double-blind randomized controlled trial, involving twenty-six KOA women that were divided equally into treatment and control groups. The treatment group was given KT and QSE, the control group received sham taping and QSE. Quadriceps muscle strength and WOMAC scores were measured before and after treatment at 4, 6 and 8 weeks. There was a significant difference in quadriceps muscle strength at the 6th week (p = 0.019) between treatment and control groups and no significant differences (p> 0.05) in the strength of quadriceps muscle at 4th and 8th weeks and WOMAC values ??at 4th, 6th and 8th weeks. We concluded that a combination of KT with QSE offers advantages for improvement of quadriceps muscle strength at 6th week but not for functional status in KOA. Keywords: Kinesio taping, Osteoarthritis, Strengthening exercises, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC)